The study on permeability ratio curve of polymer/SAA binary system and two-phase of viscous crude - Ya-nan Wang; Ji-hong Zhang (Functional Materials, 2017)
According to the different proportion of making up solution of the binary combination system which use of hydrophobic associating polymer and Sulfonate Gemini Surfactant, determinating of its viscosity and interfacial tension before injection. Simulation of the bohai suizhong 36-1 oilfield actual situation, the constant speed nonsteady state method is used for the determination of permeability ratio curve of water drive and binary combination drive, and the experimental data were processed by J.B.N. Method. Analysis of the pros and cons of existing several kinds of the viscosity processing methods for non-Newtonian fluid flow in the core, put forward a new method of viscosity processing, and compared the binary combination drive relative permeability curve which use of the different viscosity processing method. Laboratory findings show that the binary multisystem flooding in oil relative permeability is higher than water flooding, the water relative permeability is lower than water flooding, SOR is lower than water drive; Mass fraction of surfactant and polymer concentration of the binary multisystem have influence on the permeability ratio curve modality.